Structural changes in dairy business in Croatia - Teo Vujčić; Petar Bosnić (Mljekarstvo)
Croatia today is in the economy transition process that also includes agriculture aiming to increase production and achieving competitive standard with international and European markets. Currently, domestic cow milk production ensures 80% of annual milk and dairy products requirements with the 20% import. In the period from 1990-1992, during the patriot war, 103000 cows and heifers were destroyed. Since then, Croatia started the gradual process of reorganization of the agricultural private sector including dairy business in order to increase production insensitivity.The agricultural structure of dairy segment is unsatisfactory with only 23.39% of farms holding four or more heifers. Households with 3 cows per farm dominate with average real estate of 0.10-3.0 acres.Changes in milk production (1990-2003) are reflected in the decrease of the number of breeding cattle – index 56.13%, and decrease of milk market producers from 65 000 to 65 151. Never the less, positive trends towards stabilization in milk production (2003 – 642 mil litres) and annual milk intake increased from 342 mil litres in 1990 to 472 mil litres in 2003 (index 138.08%) can be noticed. Changes in the structure of milk producers show certain positive movements as 23.39% of producers have 53.40% cows and respectively participation in milk production and buy off. Until 2008, with determined development conditions, cow milk production can increase for 42% and from 2703 litres to average of 4000 litres per dairy cow.